Case report: Tall cell carcinoma with reversed polarity of the breast: an additional case and review of the literature - Lei, Zi; Wang, Ying-Xia; Wang, Zhi-Yuan; Yang, Cheng-gang; Pan, Guo-Qing (Frontiers in Oncology, 2024)
Objective: The aim of this report was to comprehensively investigate the clinicopathological features, histological characteristics, and differential diagnosis of tall cell carcinoma with reversed polarity of the breast (TCCRP) to enhance the understanding of this tumour for precise therapeutic interventions.The clinicopathological characteristics and differential diagnosis of a patient with TCCRP were retrospectively analysed, and a systematic literature review was conducted extracted from relevant published studies on PubMed.Results: All patients included in the study were female, with a median age of 51 years.Microscopically, the tumour cells exhibited a solid papillary growth pattern with tall columnar morphology and reversed nuclear polarity. Immunohistochemistry revealed that the tumours were triple-negative breast cancer (negative for ER, PR, and HER-2), with a low Ki-67 proliferation index. Different degrees of expression were observed for CK7, Calretinin, and S-100 markers; however, CK5/6 showed high expression levels.Conclusions: TCCRP is an uncommon invasive carcinoma subtype found in the breast.Its histological morphology resembles that of tall cell subtype papillary thyroid carcinoma. Accurate diagnosis requires the integration of histomorphological assessment along with immunohistochemistry and molecular genetics analysis.